2013
DOI: 10.1080/15438627.2012.757224
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Injury Affecting Competitive Collegiate Swimmers

Abstract: The purposes of this study were to determine the incidence and distribution of injuries affecting collegiate competitive swimmers and to test possible injury risk factors. A prospective cohort design was used to follow 34 swimmers (16 M, 18 F) from an NCAA Division I Midwest University over one academic year. Exposure-based injury rates were determined for both practice and competition. Risk of injury was assessed relative to gender, years swimming, and history of injury. Twenty of 34 swimmers sustained 31 inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 22 publications
2
57
1
2
Order By: Relevance
“…The urgent need for greater disclosure of non-time loss injuries is further highlighted by our study and previous studies4–6 22 25 26 finding large proportions of shoulder and overuse injuries. In addition, female swimmers were more likely to suffer an overuse injury than male swimmers.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The urgent need for greater disclosure of non-time loss injuries is further highlighted by our study and previous studies4–6 22 25 26 finding large proportions of shoulder and overuse injuries. In addition, female swimmers were more likely to suffer an overuse injury than male swimmers.…”
Section: Discussionsupporting
confidence: 61%
“…In these studies, activities outside of swimming contributed to 55–62% of injuries. A smaller study22 of 34 NCAA Division I male and female swimmers across one season restricted injuries to those sustained during school-sanctioned practices and competitions, yielding an overall rate of 5.55 injuries per 1000 AEs. Our study utilised data from 22 programmes and 53 seasons and yielded smaller swimming injury rates (men 1.48/1000 AEs; women 1.63/1000 AEs).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that gender is not a risk factor for injury or illness in aquatic disciplines5 7 8 unlike in sports such as athletics23 or football,24 where males have an overall increased injury incidence. In aquatics, the high-risk group comprises older athletes competing in HD, WP and DIV.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the International Olympic Committee (IOC) assessed injury incidence in WP during the 2004 Olympic Games,2 and investigated all aquatic disciplines during the 2008 and 2012 Olympic Games 3 6. Another prospective injury surveillance programme that has rendered interesting results was conducted by the National Collegiate Athletic Association in SW and DIV 5 7…”
Section: Introductionmentioning
confidence: 99%
“…A 1-year prospective study of male and female swimmers at an NCAA Division I university reported 5.5 injuries per 1,000 athlete exposures and 3.04 injuries per 1,000 exposure hours. Prior injuries to the same and different anatomical locations were independent risk factors for new injuries (9). The Fédération Internationale de Natation (FINA) is the international sports body responsible for the organizational oversight of competitive swimming, water polo, diving, synchronized swimming, open water swimming, and masters swimming.…”
Section: Introductionmentioning
confidence: 99%